Role of human DNA polymerase κ as an extender in translesion synthesis - Haracska, Lajos (National Academy of Sciences, 2002)
Human DNA polymerase (Pol)κ is a member of the Y family of DNA polymerases. Unlike Polη, another member of this family, which carries out efficient translesion synthesis through various DNA lesions, the role of Polκ in lesion bypass has remained unclear. Recent studies, however, have indicated that Polκ is a proficient extender of mispaired primer termini on undamaged DNAs and also on cis-syn thymine-thymine (T-T) dimer-containing DNA. Here we determine whether Polκ can promote the efficient bypass of DNA lesions by extending from the nucleotides inserted opposite the lesion site by another DNA polymerase. From steady-state kinetic analyses, we find that Polκ is highly inefficient at incorporating nucleotides opposite an O(6)-methyl guanine (m6G) lesion, but it efficiently extends from the T or C nucleotide incorporated opposite this lesion by Polδ. Opposite an 8-oxoguanine (8-oxoG) lesion, Polκ efficiently inserts an A and then proficiently extends from it. Importantly, for both these DNA lesions, however, the most efficient bypass occurs when Polδ is combined with Polκ; in this reaction, Polκ performs the extension step after the incorporation of nucleotides opposite these lesion sites by Polδ. These studies reveal a role for Polκ in the extension phase of lesion bypass.